Monitoring and Evaluation Capacities in Ghana : A Diagnosis and Proposed Action Plan - World Bank (Washington, DC, 2013)
World Bank missions to Ghana were undertaken in June and October 1999 as part of a diagnosis of M&E capacities and related development options in Ghana. The government has an ambitious program of reform to improve public sector management -reforms planned or underway include a significant downsizing of the public sector, an ongoing review of its functions and structures, a medium-term expenditure framework (MTEF), performance plans for ministries, departments and agencies, performance agreements for senior civil servants, and extensive beneficiary surveys. An important feature of Ghana is that it is a pilot country for the Comprehensive Development Framework (CDF). One of the pillars of the CDF is results and accountability, pilot countries are strongly encouraged to embrace a results based management framework and to fully embrace dialogue with civil society. The building of M&E capacities is a key vehicle to help ensure governments have the ability to measure and report on development effectiveness, to identify appropriate policy responses, and to engage civil society and NGOs more fully in these processes. Such national capacity-building also provides a counterpart to the M&E capacities of donors, which have been the focal point for results orientation in the past.